Staffing and Managing Human Resources of Higher Degree Programme of Adult Education for Inclusiveness in Universities in Nigeria (American International Journal of Education and Linguistics Research, 2020)
The status accorded to adult education among universities-based educators and researchers appears to be very low. This may be due to scanty knowledge about the discipline and wrong perception held by the bureaucrats, policy makers and administrators within and outside the university system. The Hamburg Declaration in 1997 underscores the importance of adult education when it describes it as a key to the twenty-first century. Realising the fact that adult education is needed in this 21st century, it follows that provision of higher degree programme should be well staffed and properly managed in order to produce learners that will contribute meaningfully to the development of the society. Therefore, this study entitled: “staffing and managing human resources of higher degree programme of adult education in universities in Nigeria” is embarked upon. The aim of the study is to improve human and institutional capacity for required manpower in adult education for national development. The objectives of the study include: to identify and discuss framework for staffing higher degree programme in adult education in Nigerian universities; to find out how human resources for production of higher degrees students are sourced and managed; to assess framework for ensuring inclusiveness in managing higher degree adult education programme in universities; to explore strategies that can be employed to make adult education popular and acceptable among educators and researchers in universities; to explore motivational factors for students' enrollment in adult education higher degree programme; and to examine learning delivery techniques of lecturers/faculty in higher degree programme of adult education. The work employed research design of the survey type. Seven federal and state universities offering adult education at higher degree level were sampled. Statistical instruments were employed to analyse the data collected. All the results were decided at point 05 level of confidence with appropriate degree of freedom. The study revealed that 86.3% of the respondents opined that lack of understanding of the concept of adult education prevented people from enrolling into the course in the university, while 13.7% felt otherwise. Majority of the respondents (89.8%) held that Universities in Nigeria do not discriminate against any sex (male or female) when admitting students for any education programme including adult education, while 10.2% did not.  There is significant difference in the perception of staff and students on the framework that can be used for staffing higher degree programme in adult education in Nigerian universities (X2=2.882, df=3, p > .05). There was no significant difference in the perception of staff and students on how human resources are sourced and managed for production of higher degree students in adult education programme (X2=3.741, df=3, p > .05). There was a significant difference in the perception of staff and students on learning delivery techniques of lecturers/faculty in higher degree programme of adult education (X2=9.336, df=3, p < .05). It is recommended that efforts should be made by the stakeholders to popularise the discipline of adult education with a view to making people to understand its meaning and usefulness to the growth of the society. Adequate budgetary allocation should be made by the owner universities to adult education so as to attract qualified staff, regular payment of salaries and comprehensive welfare programme.